Magnolol Attenuates Cisplatin-Induced Muscle Wasting by M2c Macrophage Activation - Lee, Chanju; Jeong, Hyunju; Lee, Hyunji; Hong, Minwoo; Park, Seon-young; Bae, Hyunsu (Frontiers in Immunology, 2020)
Cancer chemotherapy induces sarcopenia, which is a rapid loss of muscle mass that directly restricts daily activities and leads to poor quality of life and increased mortality. Although hormone-related therapies have been used to improve appetite and nutritional status, current treatments are considered palliative. Thus, the protection of skeletal muscle loss without adverse effects is essential to allow the maintenance of chemotherapy in cancer patients. Magnolol from Magnolia officinalis has several pharmacological effects including anti-cancer and anti-inflammatory activities, but the protection from muscle atrophy is not well understood. In the present study, we investigated the effects of magnolol on muscle wasting and macrophage subtypes in a cisplatin-induced sarcopenia mouse model. We showed that magnolol significantly attenuated the body weight and the muscle loss induced by cisplatin injection. The diameter of the tibialis anterior muscle was markedly increased after magnolol treatment in cisplatin-treated mice. Importantly, magnolol increased macrophage infiltration into skeletal muscle while not affecting proliferation of macrophages. Magnolol attenuated the imbalance of M1/M2c macrophages by increasing CD206+CD163+ M2c tissue reparative macrophages. Further, magnolol increased insulin-like growth factor (IGF)-1 expression. This effect was also observed in bone marrow-derived macrophages upon magnolol treatment. Taken together, magnolol may be a promising chemoprotective agent for the prevention of muscle atrophy through the upregulating M2c macrophages, which are a major source of IGF-1.